A word from our Editor-in-Chief - Mihail Aurel Titu (Nonconventional Technologies Review)
Each technological method need to complete a technological process that represents an independent component which must, however, meet the precise requirements impose to the process equal system. The systemic approach tends to become a general method of thinking, pertaining to all sciences, yet having a particularly efficient impact on technological sciences. The essential character of the systemic approach consists in its preference for the whole over the component parts, on the one hand, and in the special attention it pays to the study of the constantly changing possible connections between the components of the system, on the other hand.